Droit d'asile et nouvel ordre mondial - crispations sur la frontière : l'envers de la globalisation - Perras, Sylvie (Études internationales)

(untitled) (Institut québécois des hautes études internationales, 1994)
The fail of communist ideology and the subsequent breaking up of the old empire has allowed an acceleration of the process of world wide exchange liberalization. Population flow adapts itself to the movement naturally, helped by the development of communications, transportation and transnational networks in different parts of the industrialized world. Conflicts, wars, human rights violations and non democratic Systems also contribute extensively to increase the south-north migratory pressures. This contemporary context has led the international community to consider international migrations to be a major threat to world stability and global security. In this context, the right to seek and to enjoy a safe haven becomes a mere illusion. The survival of the right of asylum is linked to the recognition of the failure of the actual international System. The reality of today's refugee movement calls for new types of solidarities and cooperation which should be inspired by the principles of democracy and human rights protection.